Phytochemical potential of Daphne gnidium in inhibiting growth of melanoma cells and enhancing melanogenesis of B16‐F0 melanoma. (18th October 2012) - Chaabane, Fadwa; Pinon, Aline; Simon, Alain; Ghedira, Kamel; Chekir‐Ghedira, Leila
Abstract : In this study, we have investigated inhibitory capacity of ethyl acetate, total oligomer flavonoid (TOF), aqueous extracts and beta amyrin acetate, a triterpene isolated from ethyl acetate extract obtained from leaves of Daphne gnidium, on mouse melanoma (B16‐F0 and B16‐F10 cells) proliferation. Influence of these products on percentage cell distribution in cycle phases and melanogenesis was also studied. Cell viability was determined using the 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay, and flow cytometry was used to analyse effects of tested compounds on progression through the cell cycle. In addition, amounts of melanin and tyrosinase were measured spectrophotometrically at 475 nm. Ethyl acetate, TOF and aqueous extracts exhibited significant anti‐proliferative activity after incubation with the two types of tumour skin cells B16‐F0 and B16‐F10. Furthermore, cell cycle analysis revealed that cells treated with ethyl acetate and TOF extracts were arrested predominantly in G2‐M phase. Ethyl acetate extract has also the ability to enhance melanogenesis and tyrosinase activity of B16‐F0 melanoma cells. Copyright © 2012 John Wiley & Sons, Ltd.